Instrumental Motivation of English Online Learning During Pandemic Covid-19 - Putri, I Gusti Ayu Vina Widiadnya; Winarta, Ida Bagus Gde Nova (Institut Hindu Dharma Negeri Denpasar, 2021)
This study aims to identify and analysed the Instrumental Motivation of English online learning during pandemic covid-19. Teachers and learners must be consistent in carrying out learning in special conditions nowadays. A teacher has very important role in fostering student motivation to take part in online learning, so the failures in the process of transferring knowledge to students can be minimized. This research is quantitative and descriptive qualitative study to examine Instrumental motivation in online learning during pandemic covid-19. The random sampling was used in this study. The questionnaire was used as an instrument in this study. The questionnaire consists of 12 questions as a test of instrumental motivation which is divided into three different types of questions such as: academic motivation, individual motivation and social motivation. The responses obtained from the participants were classified into five categories according to Gardner's Attitude and Motivation (Jefiza, 2017), such as; strongly agree, agree, doubt, disagree and strongly disagree. It was found that the motivation of students in online learning conducted in class was to finish on time. The total mean of academic aspect is 3.61 at the moderate level. Meanwhile, for the personal aspect, it was found that the value for the total mean of the personal aspect was 3.69 at a high level, and the mean of social aspects on instrumental motivation was 3.89 at a high level. It can be shown that, the students still have high motivation in taking online learning even during the pandemic covid-19.